Enculturation and humanization in education: pro et contra - Kyshtymova, Irina (Studia Europaea Gnesnensia, 2014)
The author substantiates the proposition of productiveness of enculturation as a principle of organization of educational environment. Furthermore, a comparative analysis with humanization as the mainstream of educational transformation is performed.